Cystic duct anomaly and pancreaticobiliary maljunction mimicking choledochal cyst - Hien Duy Pham, M.D. (Journal of Pediatric Surgery Case Reports, 2020)
A choledochal cyst (CC) is an abnormal congenital dilatation of the extrahepatic or intrahepatic biliary tree and is usually diagnosed during childhood. While a magnetic resonance cholangiopancreatography (MRCP) may be helpful for the diagnosis, laparoscopy and intraoperative cholangiography might be the final tool for the diagnosis and evaluation of anatomical variant and an effective surgical treatment. Herein we report a case of a 12-year-old male whose MRCP was suggestive choledochal cyst with gallbladder agenesis. He underwent an elective laparoscopic evaluation, and the intraoperative cholangiography and findings revealed that the patient was not a choledochal cyst but that the infundibulum of the huge gallbladder directly entering the main right hepatic duct with pancreaticobiliary maljunction. This case highlights that these rare entities can mimic each other on imaging; however, a laparoscopic approach and intraoperative cholangiography serves the dual purpose of diagnosing and treating this rare pathoanatomical entity.